Application of neural stem cells in the treatment of intracerebral hemorrhage: a systematic review - Song, Ping; Shafiq, Zohaib; Jiang, Hongxiang; Cai, Qiang (Frontiers in Pharmacology, 2025)
Stroke ranks among the top global causes of death and disability, with hemorrhagic stroke accounting for 9%–27% of cases. In China, intracerebral hemorrhage (ICH) outpaces Western rates, driving adult mortality and disability. Aging populations and urbanization diversify stroke risk factors, yielding a 28-day ICH mortality rate up to 47% (Greenberg et al., 2022)—sharply higher than ischemic stroke’s 3%—with ∼75% of survivors facing permanent neurological deficits. ICH imposes heavy burdens on individuals, families, and society. Current medical and surgical treatments struggle to enhance long-term outcomes, prompting exploration of neural stem cell (NSC) transplantation. This approach replaces lost neurons via differentiation while offering anti-inflammatory, anti-apoptotic, and neuroprotective benefits. This systematic review evaluates NSC sources, delivery routes, ICH models, therapeutic mechanisms, and early clinical trials, outlining recent progress and future directions for treating hemorrhagic stroke with NSC transplantation.